Buckwheat Journey to Functional Food Sector - Pirzadah, Tanveer B.; Malik, Bisma; Tahir, Inayatullah; Ul Rehman, Reiaz (Current Nutrition & Food Science, 2020)
Background: Buckwheat (Fagopyrum spp.), a dicot pseudocereal, has an immense potential in the functional food sector pertinently due to high nutritional profile. It is a rich source of phenolic compounds, phytosterols, fagopyrins, dietary fibre, lignans, vitamins, minerals, antioxidants and unsaturated fatty acids. The buckwheat products include tea, honey, cakes, pancakes, cookies and soba noodles are gluten-free and are thus important for coeliac disease patients. Objective: The current review discusses the comparative metadata analysis of amino acids, bioactive constituents and livelihood framework of buckwheat. Conclusion: The biological value of buckwheat proteins is considerably high possessing the aminoacid score of 100 and the comparative metadata analysis revealed that it is richer in lysine, histidine and tryptophan than wheat, corn, barley and egg. Buckwheat seeds contain many fagopyritols amongst which fagopyritols A1 is an active constituent in insulin signaling and thus helps to treat diabetes and polycystic ovarian syndrome. The buckwheat crop is on decline which needs attention for its conservation, cultivation and improvement thus we present its livelihood framework for human welfare.
Keywords: ovarian syndrome